Facile growth of compositionally tuned copper vanadate nanostructured thin films for efficient photoelectrochemical water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Applied Catalysis B: Environmental, 2019)
Copper vanadates are considered as one of the most promising photoanode materials for photoelectrochemical (PEC) water splitting owing to their narrow bandgap, stoichiometry-dependent optical and electrical properties, and high stability. However, for technological applications, it is imperative to develop stoichiometrically and structurally tuned copper vanadates for improved performance. In this study, we developed a facile and one-step hydrothermal method for the synthesis of Cu2V2O7 nanoplates, Cu5V2O10 nanorods, and Cu11V6O26 micropillars on a fluorine-doped tin oxide substrate without using a seed layer. The presence of urea during the hydrothermal synthesis significantly affected the film formation and morphology of the copper vanadates. The crystallographic, chemical, and electrochemical properties of the synthesized copper vanadates were investigated. The optimized Cu2V2O7, Cu5V2O10, and Cu11V6O26 electrodes exhibited the highest photocurrent densities of ˜0.41, 0.27, and 0.076 mA cm−2 (at 1.23 V vs. reversible hydrogen electrode under 1-sun illumination) and incident photon to current efficiency values of ˜24%, 18%, and 7.5% (at 300 nm), respectively. The band edge positions of Cu2V2O7, Cu5V2O10, and Cu11V6O26 were estimated on the basis of the spectroscopic and electrochemical results. The synthesis scheme and valuable insights provided in this work can be used for the development of chemically and morphologically optimized copper vanadates for efficient PEC water splitting.
Keywords: Band edge; Copper vanadate; Incident photon-to-current efficiencies; Nano-Plate; Optical and electrical properties; Photoelectrochemical water splitting; Reversible hydrogen electrodes; Technological applications; Band edge; Copper vanadate; Nanoplate; Nanorod; Photoelectrochemical water splitting